EXPLORING TEACHERS' STRATEGIES IN IMPLEMENTING DIFFERENTIATED INSTRUCTION IN PRIMARY SCHOOLS - Maulina Dwi Yahya, Maulina Dwi Yahya; Novia Diah Ayu Perdana, Novia Diah Ayu Perdana; Inas Arifah Nurmala Sutanta, Inas Arifah Nurmala Sutanta; Azizah Putri Arseti, Azizah Putri Arseti; Adelia Dian Giendra Wahyu Wardani, Adelia Dian Giendra Wahyu Wardani; Atmojo, Setyo Eko (Fakultas Keguruan dan Ilmu Pendidikan Universitas Peradaban, 2026)
In elementary school, differentiated learning is an effective method of addressing student diversity. By using this strategy, learning content, processes, and products can be tailored to students' needs, interests, and learning readiness. It has the ability to significantly improve student motivation, engagement, and learning outcomes. The purpose of this study is to find and explain the methods used by teachers to implement differentiated learning in the classroom. Qualitative case studies are used through classroom observations, in-depth interviews, and thematic analysis. Research shows that the successful implementation of this strategy is greatly influenced by institutional support, teachers' abilities, and effective time and class management. These findings reinforce the importance of ongoing training and strategic support from schools and governments to maximize the implementation of these strategies to achieve inclusive and high-quality education. These results suggest that the application of differentiated learning can improve students' learning processes and outcomes, although this faces challenges such as time constraints and variations in students' abilities.